Efektivitas Implementasi Mobilisasi Dini dan Dampaknya Terhadap Hemodinamik Pada Pasien yang Terpasang Ventilator : Literature Review - Sesela Melin; Dewi Prabawati (Universitas Malahayati Lampung, 2026)
ABSTRACT Early mobilization is defined as the initiation of planned physical activities—such as passive and active range-of-motion exercises, sitting at the edge of the bed, transfer to a wheelchair, and ambulation within 24 to 72 hours of intensive care unit (ICU) admission or once hemodynamic stability is achieved. In critically ill patients, including those receiving mechanical ventilation, early mobilization has been associated with improved physical function, reduced duration of mechanical ventilation, shorter ICU and hospital length of stay, and potential reductions in mortality. However, its effects on hemodynamic stability remain a clinical concern. This literature review aimed to evaluate the effectiveness of early mobilization and its impact on hemodynamic parameters, including blood pressure, mean arterial pressure (MAP), heart rate (HR), respiratory rate (RR), and oxygen saturation (SpO₂), in mechanically ventilated patients. A literature review was conducted using the PICOT framework (Population, Intervention, Comparison, Outcome, and Time). Primary studies were identified through systematic searches of Google Scholar, PubMed, ScienceDirect, ResearchGate, BMC, Gale, and Portal Garuda. Articles published between 2020 and 2025 were included based on predefined eligibility criteria. Thirteen eligible studies were analyzed. Overall, early mobilization did not result in significant changes in key hemodynamic parameters, including MAP, RR, and SpO₂ (p 0.05). A modest but statistically significant increase in heart rate was consistently observed following mobilization, with mean HR rising from approximately 81 to 84 beats per minute (p 0.001). Early mobilization in mechanically ventilated, critically ill patients appears to be safe and well tolerated, with no evidence of clinically significant hemodynamic instability. Keywords: Early Mobilization, Hemodynamics, Mechanically Ventilated Patient. ABSTRAK Mobilisasi dini adalah melakukan aktivitas fisik yang direncanakan (seperti latihan rentang gerak pasif dan aktif, duduk di tepi tempat tidur, transfer ke kursi roda, dan berjalan) dalam 24 hingga 72 jam pertama sejak masuk ke ICU atau sejak hemodinamika stabil. Mobilisasi dini pada pasien kritis, termasuk pasien yang menggunakan ventilator, dapat meningkatkan fungsi fisik, memperpendek durasi ventilasi mekanik, mengurangi waktu rawat inap di ICU dan rumah sakit, dan bahkan dapat mengurangi mortalitas. Tinjauan literature review ini untuk menganalisis efektivitas implementasi mobilisasi dini dan dampaknya terhadap hemodinamik yaitu tekanan darah, MAP (Mean Arterial Pressure), HR (Heart Rate), RR (Respiration Rate) dan SP02 (saturasi oksigen) pada pasien yang terpasang ventilator. Studi literature review ini menggunakan metode pendekatan PICOT yang memiliki 5 komponen, yakni: P (patient/population), I (intervention), C (comparison), O (outcome), T (Time). Data yang digunakan merupakan data primer yang didapatkan dari beberapa database seperti : Google Schoolar, Pubmed, Science Direct, Research Gate, BMC, Gale, Portal Garuda. Pencarian literatur dalam penyusunan artikel dengan penerbitan jurnal dari tahun 2020 sampai 2025. Hasil tinjauan berdasarkan penelusuran 13 jurnal menunjukkan mobilisasi dini Sebagian besar tidak merubah hemodinamik secara signifikan, MAP (Mean Artery Pressure), RR (Respiration Rate), dan saturasi oksigen dengan nilai p 0.05, namun HR (Heart Rate) mengalami kenaikan, dari rata-rata HR 81 x/menit menjadi 84x/menit dengan nilai P 0.001. Mobilisasi dini pada pasien kritis secara umum aman dilakukan dan tidak menyebabkan perubahan hemodinamik yang signifikan. Kata Kunci: Mobilisasi Dini, Hemodinamik, Pasien Terpasang Ventilator.